The Effect of Subject Matter Knowledge Education on Pre-Service Science Teacher’s Approach to Errors - Salih Değirmenci (Journal of Educational Issues, 2024)
The aim of this research is to examine the effect of subject matter knowledge education (SMKE) on the pre-service science teachers’ approach to error about plane mirrors. This study was conducted using developmental research and phenomenology designs, which are qualitative research methods. In the study, the data were analyzed with the descriptive research method. As a result of the research, it was observed that the rate of detecting the correct or incorrect statements given by the teacher candidates increased after the SMKE. It has been revealed that many candidates, who identified the wrong solutions directed to them after the SMKE, were able to make correct statements. These show that although it is dependent on the question, SMKE contributes to the conceptual development of many candidates and their learning at a metacognitive level. Some teacher candidates participating in the research has misconceptions. These are the misconceptions given in the literature such as “the location and size of an object’s image in plane mirrors are affected by the movement of the observer”, “if there is an obstacle in front of an object, some or all of the object does not appear in the mirror”, “when we look at the plane mirror, the image of the object is formed, when we do not look, the image of the object does not form”, and “the size of the image depends on the distance of the object from the mirror”. In addition, it was revealed that a few candidates had a misconception, which was not seen in the literature, as “if the mirror size increases, the image becomes smaller”.